DIFFERENT APPROACHES TO ESTIMATE THE SUCTION HEAD AT THE WET FRONT IN THE GREEN AND AMPT WATER INFILTRATION EQUATION (Journal of Engineering, 2005)
This study was conducted to estimate the suction head at the wetting front T in the Green and Ampt infiltration equation using uniformly packed soil columns of three different - textured soils. Four different approaches were used for this estimation. Cumulative depths of infiltration I along with the visual wet front advance Z was recorded with time t. Soil water content profiles were also obtained by which the sharpness of the wet front was tested using an empirical model adopted from van Genuchten (1980) model for soil moisture-suction head relation. The Green and Ampt equation did fit the infiltration data very well with significant correlation of its parameter K with the physical measure of saturated hydraulic conductivity K. Four different methods were used to estimate t: from fitting the Green and Ampt cquation to infiltration data (I vs. t), numerical integration using hydraulic conductivity as afunction of suctionhead K() in the basic definition equation of defining t, numerical integration using conductivity as afunction of volumetric water content K(0), and from the soil sorptivity S evaluated from early time infiltration data using Philip one-term equation alons with Green and Ampt equation for horizontal infiltration No significant differences were found between these four methods in estimating t at 0.01 level. Significant differences, however, were found at the same level between the values of T for the three soils as it was expected.